The Effect of The Talking Stick Cooperative Learning Model on Science Learning Outcomes of Fifth-Grade Students - Riska Faradila; Zulnuraini Zulnuraini; Asriani Asriani; Arif Firmansyah; Sri Wahyuni (Journal of General Education and Humanities, 2026)
This study aims to determine the effect of the Talking Stick cooperative learning model on students' learning outcomes in science subjects at SDN Tindaki. The background of this research is the relatively low learning outcomes of students in science subjects. Therefore, an appropriate learning model is needed to improve students' understanding and participation during the learning process. This research employed a quantitative, pre-experimental design with a one-group pretest–posttest method. The study subjects were 16 fifth-grade students from SDN Tindaki. Data were collected through learning outcome tests, and analysis was conducted using descriptive and inferential statistics, including a t-test after satisfying normality test requirements. The results showed that the average pretest score was 56.25, while the average posttest score increased to 81.56. The results of the hypothesis test showed that the calculated t-value (13.27) was greater than the t-table value (2.131) at the 0.05 significance level. This indicates that the cooperative learning model of the Talking Stick type significantly improves students' learning outcomes in science subjects for fifth-grade students at SDN Tindaki.